(untitled) (Journal of the College of Basic Education, 2022)
The problem of the current research is based on studying the role of the multiplicity of materials in the products of the students of the Department of Family Education and the Creative Art Professions in the subject of handicrafts by addressing many products by study and analysis to know their topics, components and methods of implementation, as well as knowing their implications in light of the diversity of these materials. The aim of the current research is to: Identify the multiplicity of materials in the products of students of the Department of Family Education and Artistic Professions in the subject of handicrafts. The second chapter included the theoretical framework that the researchers divided into two topics, the first topic: the multiplicity of natural and industrial raw materials. And the second topic: experience in the use of raw materials. This chapter also included the indicators of the theoretical framework that the research reached. The third chapter included the procedures taken by the researchers to achieve the research objective. The original society of the research was determined by a set of outputs implemented by male and female students, and an intentional sample was selected for study and analysis, consisting of a group of products (4) models whose raw materials varied and diversited in an attempt to reveal their main and secondary components. The fourth chapter included the most important findings of the research.